Jerome Bruner : developing a sense of the possible - Takaya, Keiichi (SpringerBriefs in Education,, 2013)
Jerome S. Bruner (1915- ) is one of the best known and most influential psychologists of the twentieth century. He has made significant contributions to cognitive psychology and educational theory. This book presents a brief introduction to Jerome Bruner's educational ideas and details their influences on our educational discourse and practice. It examines Bruner's ideas in the context of some key educational issues in the United States since the early twentieth century. Jerome Bruner: Developing a Sense of the Possible will be an inspiration, and vital call to action, to readers looking to better understand today's instructional and curriculum theories. It will help readers gain invaluable insight into the ways teaching and schools can be improved in the future.